Inclusive Leadership From the Family Perspective in Compulsory Education - Emilio Crisol-Moya; María Asunción Romero-López; Antonio Burgos García; Yessica Sánchez-Hernández (Springer, 2022)
Distributed and pedagogical leadership plays a key role in the creation and upholding of inclusive school practices as a strategy for improvement and success in the management of quality education for students. Aims: describe, through an inclusive perspective, the actions and initiatives implemented to promote attention to diversity by school leadership teams, from the point of view of families. Methodology: Descriptive-exploratory design with a cross-sectional, quantitative focus. Sample: 25 schools (public schools, N = 18, and charter schools, N = 7) with 631 families. These families completed the questionnaire, "Leading inclusive education in compulsory-education schools-families". Results: identifying actions and strategies aimed at the prevention of truancy through a school environment that generates respect, recognition and appreciation of the different needs of their students. Conclusions: Actions taken are advancing the development of a school culture where the family plays a key role. Some of the actions implemented focus on respecting the different needs of students and the educational community in order to develop an inclusive school climate. However, schools should both make families aware of the importance and benefits and promote the participation of students and the educational community in the school.